Types, norms, and normalisation: Hormone research and treatments in Italy, Argentina, and Brazil, c. 1900–50. (April 2021) - Beccalossi, Chiara
Displacing the physiological model that had held sway in 19th-century medical thinking, early 20th-century hormone research promoted an understanding of the body and sexual desires in which variations in sex characteristics and non-reproductive sexual behaviours such as homosexuality were attributed to anomalies in the internal secretions produced by the testes or the ovaries. Biotypology, a new brand of medical science conceived and led by the Italian endocrinologist Nicola Pende, employed hormone research to study human types and hormone treatments to normalise individuals who did not conform to accepted medical norms. Latin American medical doctors, eugenicists, and sexologists took up biotypology with enthusiasm. This article considers the case studies of Italy, Argentina, and Brazil, and analyses the work of medical doctors who adopted a biotypological mode of reasoning and employed to various extents hormone therapies in their practice. By focusing on hormone therapies that aimed to normalise secondary sexual characteristics and the sexual instinct, the article suggests that while the existence of normality was contested to the point that a number of medical scientists argued that no such thing existed, the pursuit of normality was carried out in very practical terms through the new medical technologies hormone research had introduced.